Exploring youth consumer behavior in the context of mobile short video advertising using an extended stimulus–organization–response model - Tian, Kun; Xuan, Wenxia; Hao, Lijie; Wei, Wenjing; Li, Dongping; Zhu, Lu (Frontiers in Psychology, 2022)
Under the hit of the epidemic, an increasing number of young people exchange and purchase goods by watching and resorting to mobile short video advertisements. Therefore, it is of great significance to explore the influence mechanism of mobile short video advertising on the consumption behavior of young people. This study develops a theoretical framework including fashion, socialization, entertainment, personalization, brand, psychological needs, satisfaction, and consumption behavior using a stimulus–organism–response (SOR) theory. The data from 332 young people using mobile short video advertising revealed that psychological needs exerted significant impacts on satisfaction, mediating the advertisements, and consumer satisfaction. The attributes of advertising, including fashion, socialization, entertainment, personalization, and branding, significantly promote young people’s psychological needs and satisfaction. In addition, satisfaction affects consumer behavior, and in the same manner, fashion and brand attribute directly impact consumer satisfaction.